Au-delà des «vagues» #moiaussi : cinq ans de mobilisation féministe en musique au Québec (2017-2022) - Blais-Tremblay, Vanessa; Champagne, Lysandre (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2020)
Cet article dresse le portrait de cinq organisations qui militent pour l’équité en musique au Québec depuis 2017 : MTL Women in Music, Femmes* en Musique, Lotus collective MTL Coop, shesaid.so MTL et le réseau DIG! Différences et inégalités de genre dans la musique au Québec. En s’inscrivant dans la longue lignée des travaux critiques en historiographie féministe, l’article rend compte de la pluralité des mobilisations féministes au-delà des « vagues » #moiaussi qui ont ponctué l’actualité musicale québécoise au cours des cinq dernières années. Dans la seconde partie, les autrices détaillent les travaux du réseau D!G. Elles présentent des retombées initiales prometteuses à la fois pour le milieu universitaire et pour les milieux de pratique en ce qui concerne l’épistémologie et les méthodologies de la « musicologie partenariale collaborative féministe ».
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; DIG; LGBTQIA2+; amérique du nord; amériques; approches et analyses; arts; canada; discipline; femmes* artistes; genre; histoire et politique; identités LGBTQIA2+; inégalités; militance; musique; périodes historiques; québec; recherche partenariale; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail

Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis